Shared knowledge and the coagglomeration of occupations - Todd M. Gabe; Jaison R. Abel (Federal Reserve Bank of New York, 2013)
This paper provides an empirical analysis of the extent to which people in different occupations locate near one another, or coagglomerate. We construct pairwise Ellison-Glaeser coagglomeration indices for U.S. occupations and use these measures to investigate the factors influencing the geographic concentration of occupations. The analysis is conducted separately at the metropolitan area and state levels of geography. Empirical results reveal that occupations with similar knowledge requirements tend to coagglomerate and that the importance of this shared knowledge is larger in metropolitan areas than in states. These findings are robust to instrumental variables estimation that relies on an instrument set characterizing the means by which people typically acquire knowledge. An extension to the main analysis finds that, when we focus on metropolitan areas, the largest effects on coagglomeration are due to shared knowledge about the subjects of engineering and technology, arts and humanities, manufacturing and production, and mathematics and science.
Keywords: J24; O10; R12; R23; 330; coagglomeration; geographic concentration; labor market pooling; knowledge spillovers; occupations